Evaluación de tres cepas trichoderma sp, con dos métodos de siembra, para controlar damping off en balsa (Ochroma pyramidale), recinto Oronguillo-Echeandia - Vargas Montesdeoca, Washington Rubén (2017)
Balsa (Ochroma Pyramidale) is a species forestry timber that has great demand international due to its features timber and price (2.30 USD/m3). Ecuador has more than 20,000 Ha plantations between natural and reforested woods with this species, specifically in the Provinces Guayas, El Oro, Los Rios, Pichincha and Bolivar. Its propagation in nurseries and transplants is preferred perform controls preventive during first years, as are attacked by diseases fungal as "Damping off", caused by fungi Fito pathogens of genera Rhizotocnia, Fusarium, Pythium and Botrytis. Accordingly, the objective general of this research is evaluate the best endemic strain of Trichoderma sp of Province Bolívar for control Damping off in seedlings of raft, to increase its index of survival in forest nurseries, plantations and incentives to forest producers use them.. With base in results obtained in variable Percentage of Germination, Percentage of Survival, Diameter of Stem (mm), Height of Plant (cm), Volume Root (cm3), Number of Leaves, multiple comparisons tests of means Tukey, Scheffé, Orthogonal Contrasts, models mathematical Quadratic, Exponential and with a level of reliability statistics average of the 99.9 % in this research, it is concluded that best components in control Damping off in the study area are endemic species Trichoderma sp Puruguay - UEB- (B2) by its easy isolation, adaptability to climate change and quick sporulation, doses 100 (CFU, C3) due to the concentration of a large number of spores and method of planting perforated Polyethylene Bags (A1) by its capacity of moisture retention